WRITTEN CORRECTIVE FEEDBACK: SENIOR HIGH SCHOOL STUDENTS’ PERCEPTIONS AND PREFERENCES - Dinda Suci Al Aluf (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Students' perceptions and preferences for Written Corrective Feedback have been discussed in recent years. However, a deeper understanding of the reason behind students' perceptions and preferences for WCF has yet to be presented. This study tried to reveal a more profound understanding of the two perceptions toward WCF from students' points of view. Moreover, their preferences about the application of WCF were discussed. Through the survey study, how the majority of students perceive and prefer WCF would be seen from the questionnaire. This result provides a guideline topic for the interview. The findings revealed that most students perceive WCF positively. Also, they confirmed that WCF gave them confidence and helped them understand the material given. Whereas those with a negative attitude emphasized the importance of providing praise, explaining the error, and using Indonesian in providing WCF. Furthermore, the findings showed that direct metalinguistic and comprehensive WCF were more favoured. In addition, they preferred WCF to be provided digitally. Not only that, students considered paragraph organization as the most crucial aspect to be corrected. In conclusion, students show a positive attitude towards WCF. However, to optimize its function, students' preferences and evaluations must be considered.